Huddersfield's roll of honour : 1914-1922 - Stansfield, J. Margaret (Book collections on Project MUSE., 2014)
Huddersfield's Roll of Honour 1914-1922 is a detailed account of 3,439 service personnel from Huddersfield who lost their lives during the First World War.